18F-Fluorodeoxyglucose Positron Emission Tomography Parameters can Predict Long-Term Outcome Following Trimodality Treatment for Oesophageal Cancer. Issue 3 (March 2023) - Abraham, A.G.; Riauka, T.; Hudson, M.; Ghosh, S.; Zebak, S.; Alba, V.; Vaihenberg, E.; Warkentin, H.; Tankel, K.; Severin, D.; Bedard, E.; Spratlin, J.; et al.
Abstract: Aims: 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 FDG-PET/CT) is routinely used for the pre-treatment staging of oesophageal or gastro-oesophageal junction cancers (EGEJC). The aim of this study was to identify objective 18 FDG-PET/CT-derived parameters that can aid in predicting the patterns of recurrence and prognostication in patients with EGEJC. Patients and methods: EGEJC patients referred for consideration of preoperative chemoradiation therapy were identified and clinicopathological data were collected. 18 FDG-PET/CT imaging data were reviewed and correlated with treatment outcomes. Maximum standardised uptake value (SUVmax ), metabolic tumour volume (MTV) and total lesion glycolysis were assessed and association with recurrence-free survival (RFS), locoregional recurrence-free survival (LR-RFS), oesophageal cancer-specific survival (ECSS) and overall survival were evaluated using receiver operating characteristic curves, as well as Cox regression and Kaplan–Meier models. Results: In total, 191 EGEJC patients completed trimodality treatment and 164 with 18 FDG-PET/CT data were included in this analysis. At the time of analysis, 15 (9.1%), 70 (42.7%) and two (1.2%) patients were noted to have locoregional, distant and both locoregional and distant metastases, respectively. The median RFS was 30 months (9.6–50.4) and the 5-year RFS was 31.1%. The 5-year overall survival and ECSS were both noted to be 34.8%. Pre-treatment MTV25 > 28.5 cm 3 ( P = 0.029), MTV40 > 12.4 cm 3 ( P = 0.018) and MTV50 > 10.2 cm 3 ( P = 0.005) predicted for worse LR-RFS, ECSS and overall survival for MTV definition of voxels ≥25%, 40% and 50% of SUVmax . Conclusion: 18 FDG-PET/CT parameters MTV and total lesion glycolysis are useful prognostic tools to predict for LR-RFS, ECSS and overall survival in EGEJC. MTV had the highest accuracy in predicting clinical outcomes. The volume cut-off points we identified for different MTV thresholds predicted outcomes with significant accuracy and may potentially be used for decision making in clinical practice. Highlights: 18 FDG-PET/CT is routinely used for staging oesophageal or gastro-oesophageal junction cancers. Total lesion glycolysis (TLG) and metabolic tumour volume (MTV) are parameters useful for prognostication. MTV can predict recurrence and survival patterns with significant accuracy.